2022
DOI: 10.3390/antiox12010010
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-MS Chemical Fingerprinting and Antioxidant, Enzyme Inhibition, Anti-Inflammatory In Silico and Cytoprotective Activities of Cladonia chlorophaea and C. gracilis (Cladoniaceae) from Antarctica

Abstract: The lichen species Cladonia chlorophaea and C. gracilis (Cladoniaceae) are widely distributed in the island archipelago of maritime Antarctica and represent a natural resource of scientific interest. In this work, the metabolomic characterization of the ethanolic extracts of these species and the determination of the antioxidant activity, enzymatic inhibition and anti-inflammatory potential of selected compounds on the 5-lipoxygenase enzyme by molecular docking and cytoprotective activity in the SH-SY5Y cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Torres‐Benítez et al . showed that ethanol extracts of Cladonia chlorophaea and Cladonia gracilis (Cladoniaceae) had higher inhibition of α‐glucosidase compared to reference acarbose 67 . Aanachi et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Torres‐Benítez et al . showed that ethanol extracts of Cladonia chlorophaea and Cladonia gracilis (Cladoniaceae) had higher inhibition of α‐glucosidase compared to reference acarbose 67 . Aanachi et al .…”
Section: Resultsmentioning
confidence: 99%
“…66 Torres-Benítez et al showed that ethanol extracts of Cladonia chlorophaea and Cladonia gracilis (Cladoniaceae) had higher inhibition of ⊍-glucosidase compared to reference acarbose. 67 Aanachi et al reported that methanol extract showed the best inhibition against tyrosinase among Pelargonium graveolens methanol, dichloromethane and hexane extracts. 68 Tlili and Sarikurkcu studied ⊍-amylase and ⊍-glucosidase inhibition in water extracts of the five medicinal species (Camellia sinensis L., Erica arborea L., Ilex paraguariensis A. St. Hilaire, Rosmarinus officinalis L., and Thymus vulgaris L.).…”
Section: Characterization Of Phenolic Content By Lc-hrmsmentioning
confidence: 99%
“…Molecular docking was performed using the respective rigid crystallographic enzyme structures and the flexible ligands whose torsion angles were identified (for 10 independent urns per ligand). Targeted coupling was performed using the UCSF Chimera program [ 28 , 29 ] taking the reference inhibitor galantamine for acetylcholinesterase and butyrylcholinesterase as the catalytic site. Polar hydrogens and Gasteiger partial charges were added for the docking process; a grid chart was created using the Autodock Vina tools in the UCSF Chimera software.…”
Section: Methodsmentioning
confidence: 99%
“…The results obtained from molecular docking were analyzed and visualized in the Discovery Studio Visualizer software [ 30 ]. Once the molecular docking was done, the best conformation at the catalytic site was analyzed by evaluating the best hydrogen bonding interactions or π interactions, including the free ligand binding energy (kcal/mol) [ 29 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…[31][32][33] In the lichen ́s research, LC-MS has been applied to characterization, untargeted/targeted screening, quantification and dereplication of lichen ́s substances based on the structure fragmentation. 16,34 Analysis of lichens based on LC-ESI/MS/MS including species of the genus Cetraria, 35 Cladonia, 36,37 Evernia, 38 Lecania, Pseudephebe, 39 Ramalina, 40 Sphaerophorus, 39 Sticta, 19 Umbilicaria, 41 Usnea, 29 Xanthoparmelia, 42 and Parmotrema, 6,7 have been reported. According to previous chemical studies of the Parmotrema genus, 6,7,18,20,[24][25][26]30,43 we show the chemistry of this genus based on characteristic lichen compounds, such as depsidone, depsidone, and diphenylether found in P Perlatum, as shown in Table 2.…”
Section: Dibenzofuranmentioning
confidence: 99%